2010
DOI: 10.1002/jbmr.185
|View full text |Cite
|
Sign up to set email alerts
|

Fracture healing is accelerated in the absence of the adaptive immune system

Abstract: Fracture healing is a unique biologic process starting with an initial inflammatory response. As in other regenerative processes, bone and the immune system interact closely during fracture healing. This project was aimed at further elucidating how the host immune system participates in fracture healing. A standard closed femoral fracture was created in wild-type (WT) and recombination activating gene 1 knockout (RAG1 À/À ) mice lacking the adaptive immune system. Healing was investigated using micro-computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(125 citation statements)
references
References 59 publications
7
111
0
Order By: Relevance
“…Taken together, our data demonstrate for the first time that osteomacs are an integral cellular component of osteal tissues during bone healing and implicate osteomacs as critical participants in intramembranous ossification during bone repair. The identification of this novel osteoimmunologic mechanism expands our understanding of the substantial contributions the immune system has on bone/callus outcomes during fracture repair (59,60) and provides a new research avenue for manipulating bone formation for therapeutic applications. Identification of osteomac-derived anabolic factors ultimately may lead to new approaches to improve fracture healing and reverse skeletal damage after pathologic bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data demonstrate for the first time that osteomacs are an integral cellular component of osteal tissues during bone healing and implicate osteomacs as critical participants in intramembranous ossification during bone repair. The identification of this novel osteoimmunologic mechanism expands our understanding of the substantial contributions the immune system has on bone/callus outcomes during fracture repair (59,60) and provides a new research avenue for manipulating bone formation for therapeutic applications. Identification of osteomac-derived anabolic factors ultimately may lead to new approaches to improve fracture healing and reverse skeletal damage after pathologic bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the uncontrolled stimulation of B and T lymphocytes appear to be important in delayed bone healing. RAG -/-mice, which lack T and B cells, show an enhancement of callus mineralisation and bone remodelling and acceleration of the fracture healing (42). These effects were associated with a lower level of pro-inflammatory cytokines, TNF-, IFN-, IL-2 and IL-4 at local fracture tissues (42).…”
Section: T and B Lymphocytesmentioning
confidence: 99%
“…RAG -/-mice, which lack T and B cells, show an enhancement of callus mineralisation and bone remodelling and acceleration of the fracture healing (42). These effects were associated with a lower level of pro-inflammatory cytokines, TNF-, IFN-, IL-2 and IL-4 at local fracture tissues (42). Activated T lymphocytes are known to release RANKL, which enhance osteoclast differentiation from their progenitors and consequently induce the bone lysis (156).…”
Section: T and B Lymphocytesmentioning
confidence: 99%
“…Additionally, Cho et al demonstrated that resident macrophages (osteal) are significantly involved in parathyroid hormone-dependent bone healing [15]. Although there are no experimental models for NK cell depletion in factures, an important role of NK cells during bone repair has been implied when a high level of interferon-gamma (IFN-g) was detected in the diaphyseal regions of fractured femur in mice lacking T-and B-lymphocytes [16]. Conversely, as shown in immune-compromised animal model, bone marrow (BM) transplantation greatly enhanced the process of bone healing [17].…”
Section: Introductionmentioning
confidence: 99%